Modification of the Salasaca graphic production and its expression in tapestry - Larrea Solórzano, Andrea Daniela (Base Diseño e Innovación, 2023)
The concepts of object ecology, domology and subjective cultural legacy, as constituent axes of the aesthetic culture of a people, become evident when analyzing the iconographic transformations that took place in the Salasaca tapestries between 1960 and 2018, as a result (among other conditioning factors) of the migratory processes that this people went through during this period, fundamentally with its massive transfer from the Ecuadorian Andes to the Galapagos Islands. By means of a photographic compilation, and through a comparative process that runs hand in hand with the analysis of the life histories of the weavers of this community, the transformations in the iconography expressed through this medium can be explained.